Resisting Erasure: Representations of Palestinian Struggle in Ghassan Kanafani’s Short Stories - Februansyah, Rizki; A. Sayuti, Suminto; Suryaman, Maman (International Journal of Language and Literary Studies, 2025)
This article explores the theme of Palestinian resistance against Israeli colonization through a literary analysis of selected short stories by Ghassan Kanafani. Employing a postcolonial framework, the study examines how resistance is articulated in both overt and subtle forms—ranging from armed struggle to everyday social defiance. The stories analyzed include Paper from Ramleh, The Child Borrows His Uncle’s Gun and Goes East to Safad, Dr. Qassim Talks to Eva About Mansour Who Has Arrived in Safad, The Child, His Father, and the Gun Go to the Citadel at Jaddin, Abu Hassan Ambushes an English Ambulance and Guns in the Camp. These narratives present various representations of resistance: through the suffering of women and children, symbolic and physical sacrifices by individuals, and the moral and ideological tensions within Palestinian society. Kanafani’s portrayal of child figures and community elders illustrates how resistance is both inherited and redefined across generations. The study concludes that Kanafani’s work serves not only as a literary reflection of Palestinian struggle, but also as a powerful instrument for reclaiming identity, dignity, and collective memory in the face of systemic erasure.